Meningkatkan Hasil Belajar Gerak Dasar Manipulatif Melempar dan Menangkap Bola Melalui Pendekatan Bermain Konsep TARL - Ghofur, Abdul; Rohman, Abdur; Rahmatulloh, Achmad David; Ayyubi, Achmad Firdhaus Al; Saputra, Aditya Galih; Dinata, Vega Candra; Widodo, Atmojo Prayogo (MAN Insan Cendekia Jambi, 2025)
This study aims to improve the learning outcomes of fundamental manipulative movements, particularly the skills of throwing and catching a ball, among first-grade students of UPT SDN 222 Gresik through a play-based approach with the Teaching at the Right Level (TaRL) concept. The method used is Collaborative Classroom Action Research (CCAR) with 41 student participants. Data collection was conducted through observation, interviews, and learning outcome tests carried out in the pre-cycle, cycle 1, and cycle 2. Data analysis was performed using both quantitative and qualitative methods. The results of the study showed a significant improvement in students' fundamental manipulative movement skills, with the number of students in the Less Proficient category decreasing from 73.17% to 9.76%, while the Highly Proficient category increased from 0% to 48.78%. The play-based learning approach with the TaRL concept has been proven to create a more enjoyable and interactive learning environment, thereby increasing students' motivation and understanding in mastering basic motor skills. In conclusion, this approach is effective in overcoming students' difficulties in fundamental manipulative movements and improving overall learning outcomes. These findings can serve as a reference for Physical Education (PJOK) teachers in implementing more innovative and student-centered learning strategies.